Design and implementation of integrated tactical mobility testbed - Choi, Hongrok; Seo, Sangwon; Jung, Daeyoung; Pack, Sangheon; Kang, Minwook; Chung, Yunwon; Joo, Hyungjun; Kang, Kyungran (ICT Express, 2021)
In tactical environments, mobility has a significant impact on the performance such as handover delay. In this paper, we design and implement an integrated tactical mobility testbed that consists of (1) host identify protocol module for secure initial registration, (2) Proxy Mobile IPv6-based distributed mobility management module for infrastructure-based mobility cases, and (3) delay/disruption tolerant networking module for opportunistic mobility cases. The implementation and experimental results demonstrate that the integrated testbed can be used to consider diverse tactical mobility scenarios and to evaluate the handover performance.
Keywords: DMM; DTN; HIP; PMIPv6; Tactical mobility testbed